Diagnostic markers in schistosomiasis - A. M. Deelder (Memorias do Instituto Oswaldo Cruz, 1992)
In the present paper a brief overview will be given of the recent progress and trends in assaying diagnostic markers in schistosomiasis; only markers of the humoral immunological system and biochemical markers will be discussed, as markers for cellular immunological reactivity will be discussed by other authors. The following diagnostic markers will be reviewed: markers for infection, markers for immunity and markers for morbidity.